Analisis Recruitment Online pada PT. Tri Jaya Teknik Karawang - Alfiansyah, Ilham Ismo; Suherman, Enjang; Khalida, Laras Ratu (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the current era of globalization, ever-developing computer and internet technology always makes everything easier, including the recruitment process. The aim of this research is to find out, analyze and explain how online and offline recruitment is analyzed. The research design used in this research is descriptive research with a descriptive qualitative approach, and observations in the company environment, by interviewing several people in the company according to the data requirements. This research was carried out at PT. Tri Jaya Teknik Karawang which is located on Jl. Alternative Krajan II Ds. Warung Bambu Kec. Karawang. Researchers used the IPO (Input Process Output) method, interviews were obtained from the company's HR department. Online recruitment analysis uses Google Drive to collect data files and online tests, then uses Zoomeet for Keywords : Interview,Online, Technology,Recruitment